2022
DOI: 10.1038/s41598-022-08185-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-206 conjugated gold nanoparticle based targeted therapy in breast cancer cells

Abstract: MicroRNAs (miRNAs) are single-stranded, non-coding, 19–25 nucleotide RNA molecules that have been observed to be dysregulated in many diseases including cancer. miRNAs have been known to play an important role in cellular proliferation, differentiation, migration, apoptosis, survival, and morphogenesis. Breast cancer is heterogeneous in nature and contributed extensively to the increased mortality rate. miRNA can either be tumor-suppressive or oncogenic in nature. The level of expression of miRNA changes accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Furthermore, inorganic materials such as gold, graphene oxide, iron oxide and silica‐based materials are also capable of delivering miRNA. Chemically‐modified versions of gold particles with thiols, amino groups, and PEG have been utilized to deliver miRNA (Chaudhari et al, 2022; Fu et al, 2019). Modified anti‐miR‐155 with thiols was successfully delivered into a diabetic mouse model (Jia et al, 2017).…”
Section: Challenges and Strategies In Deploying Mirna Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inorganic materials such as gold, graphene oxide, iron oxide and silica‐based materials are also capable of delivering miRNA. Chemically‐modified versions of gold particles with thiols, amino groups, and PEG have been utilized to deliver miRNA (Chaudhari et al, 2022; Fu et al, 2019). Modified anti‐miR‐155 with thiols was successfully delivered into a diabetic mouse model (Jia et al, 2017).…”
Section: Challenges and Strategies In Deploying Mirna Therapeuticsmentioning
confidence: 99%
“…Modified anti‐miR‐155 with thiols was successfully delivered into a diabetic mouse model (Jia et al, 2017). Additionally, modification of the gold surface with PEG allows miR‐206 delivery to breast cancer cells (Chaudhari et al, 2022). Another study has shown the potential use of dextran‐coated iron oxide‐based nanoparticles to deliver miR‐29a to breast cancer cells (Yalcin, 2019).…”
Section: Challenges and Strategies In Deploying Mirna Therapeuticsmentioning
confidence: 99%
“…For instance, PEGylated gold nanoparticles were conjugated with a miR-206 mimic and tested on breast cancer cells in vitro , showing effective treatment by targeting the NOTCH 3 gene and arresting cells in the G0-G1 phase . In another study by Dang et al , the authors designed photoresponsive gold nanoshells conjugated to miR-34a to overcome the lack of specificity and efficacy observed in other studies.…”
Section: Gold Nanoconjugates To Restore Mirna Functionmentioning
confidence: 99%
“…For instance, PEGylated gold nanoparticles were conjugated with a miR-206 mimic and tested on breast cancer cells in vitro , showing effective treatment by targeting the NOTCH 3 gene and arresting cells in the G0-G1 phase. 27 In another study by Dang et al , the authors designed photoresponsive gold nanoshells conjugated to miR-34a to overcome the lack of specificity and efficacy observed in other studies. These nanocarriers released the miRNA upon stimulation with near-infrared light which led to a regulation of its downstream targets and decreased the function of triple negative breast cancer cells, namely their viability, proliferation, and motility.…”
Section: Gold Nanoconjugates To Restore Mirna Functionmentioning
confidence: 99%
“…Metal-based nanoparticles also can be used for miRNA delivery [ 145 ]. The gold nanoparticle is another attractive material for nucleic acid delivery.…”
Section: The Delivery Strategy Of Mirna-associated Immunotherapymentioning
confidence: 99%